Plasticity of parahydrogen with reduced deuterium contents: Quantum Crystals - Alekseeva, L.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
The plasticity of solid parahydrogen with lowered deuterium contents under step-wise uniaxial extension at liquid helium temperatures 1.8–4.2 K has been investigated. Work hardening curves for single crystals have been measured. Maximum possible values of sample’s elongation without their fracture at minimum stress values have been reached. Features of super-plastic irreversible deformation of samples were observed. Anomalous temperature dependence of deformation parameters has been found. The character of this anomaly exhibits evidence of the coherent motion of dislocation kinks in Pierls relief, modified by residual ortho- and deuterium impurities.